The Effect Of The Project Based Learning Model With Poster Media And Ice Breaking On Ipas' Interest In Learning - Siti Nuratnaaiko; Erwin Nurdiansyah; Supriadi Supriadi (Program Studi Pendidikan Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2026)
The low learning interest of elementary school students toward Natural and Social Sciences (IPAS) is a challenge that needs to be addressed through innovative teaching approaches. This study aims to examine the effect of the Project Based Learning (PjBL) model supported by poster media and ice breaking activities on the IPAS learning interest of fourth-grade students at SD Nurul Muttahid. Employing a one-group pretest-posttest experimental design, the study involved 20 students selected through simple random sampling from a population of 134. Data were collected using a 20-item multiple-choice test and observation sheets, and analyzed through descriptive and inferential statistics, including the Paired Samples T-Test. Results revealed a significant increase in mean learning interest scores from 77.25 (pretest) to 98.25 (posttest), with a t-value of 13.591 exceeding the critical t- table value of 2.093 (p < 0.05). The findings confirm that the integration of PjBL with poster media and ice breaking activities significantly enhances students' learning interest in IPAS.